Alpha burst activity during human REM sleep: descriptive study and functional hypotheses - Cantero, José Luis; Atienza, Mercedes (Clinical neurophysiology, 2000)
Objectives: Spectral power contribution in the range of alpha activity is a well-known electrophysiological feature of human REM sleep, which could be caused by the spontaneous bursts of alpha activity not associated with arousals that usually appear during this brain state. The present study was undertaken to determine the density of alpha bursts during tonic and phasic (oculomotor) REM periods for each REM cycle. In addition, this phasic brain event was also described from a spectral and topographical point of view. Methods: Ten healthy right-handed subjects (5 females) aged 19–25 years (mean 22.9 years, SD 2.6) participated in the present study. Each selected subject filled in a daily sleep log for 2 weeks before the experimental night to provide information on all 3 salient aspects of sleep pattern, sleep experience and sleep effects. Results: The results revealed that transient REM-alpha bursts, which lasted about 3 s and were accompanied by no increase in the EMG amplitude, appeared in all subjects who participated in this study, showing a higher density in the third and fourth REM cycle during phasic in comparison with tonic periods. The bandpass filtered signals showed the highest spectral contribution for the slower alpha components (8–9 Hz), the occipital scalp regions being the main generator source of this brain activity. Conclusions: The authors hypothesize that REM-alpha bursts may work as micro-arousals (or incomplete arousals) facilitating the brain connection with the external world in this cerebral state, whereas REM-alpha arousals – usually longer and accompanied by changes in the EMG amplitude – generate a shift of brain state associated with sleep fragmentation (complete arousal).